Interactive-Multimedia Reading Comprehension Package (IMRCP) / Assoc. Prof. Dr. Othman Ismail, Noraini Ahmad Basri and Prof. Dr. Ahmad Redzuan Abd rahman - Ismail, Othman; Ahmad Basri, Noraini; Abd rahman, Ahmad Redzuan (Research Management Institute (RMI), 2012)
This research project is based on an FRGS 2010 grant awarded for the design, development and production of an Interactive Multimedia Reading Comprehension Package (IMRCP), geared towards enhancing learners' reading skills. Two development stages were undergone before the completion of this research project. That is, the first stage of the project involved the development and customization of the English reading materials into becoming interactive multimedia learning resources; and, the second stage involved testing out the effectiveness of the IMRCP CD with UiTM L2 fulltime and distance learners taking Introductory and Intermediate English reading courses. Instructional System Design (ISD) models have constantly been referred to in the development of effective instructional activities (Dick, Carey & Carey, 2009). Many ISD models - such as the ADDIE and ASSURE models (Clayton, 2006), Dick & Carey, Morrison & Kemp (Morrison, Ross & Kemp, 2004) and Gagne Nine Events of Instruction, provide clear guidance and systematic principles that facilitate effective instructions. With proper execution of these ISD systematic principles, effective and interactive multimedia teaching and learning packages can be developed and produced. Planned needs analysis, achievable learning outcomes, careful selection of media and materials, active engagement of participants, frequent practices with immediate feedback and reinforcement are some of the ISD systematic principles that must be carefully considered and executed to ensure meaningful learning experiences can be achieved. Gagne Nine Events of Instruction is one of the many ISD models that can be utilized in designing and developing an interactive Multimedia Instructional Package (/-MIP). Gagne proposes the following Nine Events - gain attention, inform learners of objectives, stimulate recall of prior learning, present the content, provide learning guidance, elicit performance (practice), provide feedback, assess performance and enhance retention and transfer to the job (Faryadi, 2007)…